U.S. Monetary Shocks and Global Stock Prices - Laeven, Luc (IMF Working Papers; Working Paper, 2010)
This paper studies how U.S. monetary policy affects global stock prices. We find that global stock prices respond strongly to changes in U.S. interest rate policy, with stock prices increasing (decreasing) following unexpected monetary loosening (tightening). This impact is more pronounced for sectors that depend on external financing, and for countries that are more integrated with the global financial market. These findings suggest that financial frictions play an important role in the transmission of monetary policy, and that U.S. monetary policy influences global capital allocation.